Pengembangan Aplikasi Workgroup untuk Berbagi Ide dan Diskusi di Fakultas Teknik UNDIP - Iman Satoto, Kodrat; Kridalukmana, Rinta (Jurnal Sistem Komputer, 2013)
Abstract – Nowadays, information technology is used to support many kinds of organization activities. In education organization, such as Engineering Faculty of Diponegoro University, one of many activities that needs to be supported by application is about to share idea and discussion between people who collaborates in there. To support this kind of activity, web based application is one solution that can be build considering of the raise of Web 2.0 technology which enable people to interact each other and shares many kind of digital resources. Developed using CodeIgniter Framework, this application will also support sending broadcast information via email and short message service (SMS). In this paper, this application is mentioned as workgroup application